Treatment with acetate during late pregnancy protects dams against testosterone-induced renal dysfunction - Lawrence A. Olatunji; Emmanuel D. Areola; Taofeek O. Usman; Olufunto O. Badmus; Kehinde S. Olaniyi (Heliyon, 2021)
Cardiometabolic diseases are complicated by renal damage. Gestational hyperandrogenism causes gestational metabolic dysfunction that is associated with fetal and maternal tissue derangements as well as post-partum maternal androgen excess. Acetate (Ace) conferred hepatoprotection in pregnant rats exposed to excess testosterone (Tes). The effect of excess androgenic exposure on maternal kidney during and after pregnancy is not clear. Therefore, this study investigated the effect of late gestational and post-gestational testosterone exposure on renal functions and plausible renoprotective role of gestational Ace treatment in dams. Thirty pregnant Wistar rats were grouped (n = 10/group) and treated (sc) with olive oil, testosterone propionate (0.5 mg/kg) with or without acetate (200 mg/kg sodium acetate; p.o) between gestational days 14 and 19. Data were obtained from half of the animals on gestational day 20. Data were also obtained from the other half (dams) after treatment of animals which received Tes with or without prior gestational acetate treatment with post-gestational Tes (sc; 0.5 mg/kg) for the last 6 days of an 8-week postpartum period. Biochemical and statistical analyses were performed with appropriate methods and SPSS statistical software respectively. Late gestational excess Tes led to low placental weight (p = 0.0001, F = 205.7), poor fetal outcomes, creatinine (p = 0.0001, F = 385.4), urea (p = 0.0001, F = 300.9) and renal uric acid (UA) (p = 0.0001, F = 123.2), gamma-glutamyl transferase (GGT) (p = 0.004, F = 26.9), malondialdehyde (p = 0.0001, F = 45.96), and lactate dehydrogenase (LDH) (p = 0.0002, F = 150.7). Postpartum Tes exposure also caused elevated plasma testosterone (p = 0001, F = 22.15), creatinine (p = 0.0002, F = 15.2), urea (p = 0.01, F = 13.8) and renal UA (p = 0.0001, 226.8), adenosine deaminase (p = 0001, F = 544.7), GGT (p = 0.0002, F = 401.4) and LDH (p = 0.01, F = 23.7). However, gestational acetate treatment ameliorated the renal effects of gestational and post-gestational Tes exposure. Taken together, gestational acetate would pre-programme dams against renal dysfunction caused by Tes exposure.